2002
DOI: 10.1111/j.1467-842x.2002.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

The Air We Breathe: Social determinants of smoking among parents with infants

Abstract: Objectives : To estimate the smoking prevalence among parents of infants and examine these parents' socio‐demographic characteristics. Method : The sample of all parents of infants (669 mother‐father pairs, 90 single parents) was derived from the 1995 Australian Health Survey. Data were collected by face‐to‐face interview in the respondent's home. Socio‐demographic measures include parent's age, family structure, age‐left‐school, highest post‐school qualification, occupation, and family income. Results : T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
11
0
4
Order By: Relevance
“…For the purposes of this study, the original nine-level ASCO was re-coded into three categories: managers and professionals (managers and administrators, professionals and associate professionals); white-collar employees (clerical, sales and service); and blue-collar workers (trades, production workers, labourers). In other studies, this three-level indicator has been shown clearly to discriminate between occupation groups in terms of a range of health and social outcomes 32,33 . An additional category, 'not in the labour force', was also created and included the retired, persons doing home duties on a full-time basis, the unemployed, those unable to work and students.…”
Section: Measures Of Socio-economic Positionmentioning
confidence: 72%
“…For the purposes of this study, the original nine-level ASCO was re-coded into three categories: managers and professionals (managers and administrators, professionals and associate professionals); white-collar employees (clerical, sales and service); and blue-collar workers (trades, production workers, labourers). In other studies, this three-level indicator has been shown clearly to discriminate between occupation groups in terms of a range of health and social outcomes 32,33 . An additional category, 'not in the labour force', was also created and included the retired, persons doing home duties on a full-time basis, the unemployed, those unable to work and students.…”
Section: Measures Of Socio-economic Positionmentioning
confidence: 72%
“…While only 0.5% of the general Australian population had seven or more people resident in 3‐bedroom dwellings in 1996, 31 this was the norm for 54% of our children. The proportion passively exposed to cigarette smoke (68.5%) is also much higher than smoking prevalence among parents of infants in the general population (28.9%) 32 . These data underscore the need to address economic, social and environmental inequities faced by the Aboriginal population.…”
Section: Discussionmentioning
confidence: 93%
“…However, our sample was older and had higher education and income level than might be expected in the general population of smoking women. Young maternal age, lower socioeconomic status, and lower maternal education level have been reported to be predictors of smoking (Beck et al, 2002;Centers for Disease Control and Prevention [CDC], 2001;Turrell, Battistutta, & McGuffog, 2002).…”
Section: Discussionmentioning
confidence: 97%